Monody Monody - Maria Jandyra Cunha (Ilha do Desterro, 2008)
MONODY is a new poetic version of an old story of the
former Lake Lahotan - and, at the same time, an old
account of an up-dated story - the story of the Great
Basin, Nevada's desert. The magic of these poems is due
exactly to the fact that you penetrate the desert and dream
of what could have been a hundred thousand years ago. You
go back and forth, waking and dreaming. You see the ancient
lake and then you are back into the desert.
There is a lot of rhythm in these poems and they were
meant to be read slow because slow was the geological develop ment. MONODY should even be read aloud so that you can feel the changes in Nature from the lightness and balance of the waters to the dryness and compactness of the rocks. As William L. Fox himself says, MONODY is "a poem in which a mourner bewails someone's death'. And in fact, as the lake becomes sand flat, as the fresh water changes into salt,you feel rather melancholy: the water is gone and with it the animals and vegetation: life is gone and with it fertility,
criativeness , sensibility.